STRATEGI KEPUTUSAN INVESTASI PERUSAHAAN GOTO DALAM MENGHADAPI KRISIS VALUASI PASCA PANDEMI - Tuti Sriwedari; Nabila Kesya Azzahra Siregar; Ayu Primsa br Tarigan; Dira Febrina br Sebayang; Rahman Rahman; Muhammad Rayhan Satria (Jurnal Akuntansi dan Bisnis, 2026)
This study analyzes the investment strategies implemented by PT GoTo Gojek Tokopedia Tbk (GoTo) in response to the post-pandemic valuation crisis. Using a qualitative descriptive approach based on secondary data and literature review, this research examines how GoTo realigned its investment direction amid market pressures. Findings indicate that GoTo successfully transitioned from aggressive expansion to a more selective and efficiency-oriented strategy. Key measures included cost control, portfolio restructuring, and strengthening financial fundamentals through disciplined cash flow management and zero-based budgeting. The company also leveraged digital innovation and business diversification, particularly in fintech and logistics, to create recurring income and enhance ecosystem synergy. As a result, GoTo improved cost efficiency, restored investor confidence, and achieved its first annual underlying profit. This study concludes that adaptive investment strategies balancing growth and profitability are essential for tech companies facing valuation corrections. The case of GoTo provides valuable insights for other digital firms navigating post-crisis economic uncertainty while pursuing long-term sustainability